Clinical And Bacteriological Impact Of Clarithromycin In Streptococcal Pharyngitis: Findings From A Meta-Analysis Of Clinical Trials - Hoban DJ; Nauta J (Dove Medical Press, 2019)
Daryl J Hoban,1 Jos Nauta2 1Department of Medical Microbiology and Infectious Disease, Max Rady College of Medicine, University of Manitoba, Winnipeg, Manitoba, Canada; 2Department of Innovation & Development, Established Pharmaceuticals Division, Abbott Healthcare Products B.V., Weesp 1381 CP, The NetherlandsCorrespondence: Jos NautaDepartment of Innovation & Development, Established Pharmaceuticals Division, Abbott Healthcare Products B.V., C.J. van Houtenlaan 36, Weesp 1381 CP, The NetherlandsTel +31 294 47 7360Email jos.nauta@abbott.comIntroduction: Among the bacterial upper respiratory tract infections (UTRIs), the most medically significant is pharyngitis due to Group A beta-hemolytic Streptococci (GABHS). A 2012 meta-review and a 2016 Cochrane systematic review reported favorably on the comparative efficacy and safety of clarithromycin in pediatric patients with URTIs and in adults with GABHS pharyngitis. In this paper, the evidence base for clarithromycin in patients with URTIs is augmented by a meta-analysis of comparative studies in GABHS pharyngitis.Methods: A series of five outpatient trials of clarithromycin for the treatment of streptococcal pharyngitis from an internal database were subjected to meta-analysis. Active comparators comprised penicillin VK and erythromycin.Results: Rates of clinical cure or improvement were very similar in all treatment assignments, but the rates of bacteriological cure were numerically higher with clarithromycin than with comparator antibiotics. Adverse events data indicated that clarithromycin was generally well tolerated in these studies, with a relatively low incidence of adverse events and few severe incidents.Discussion: Though currently not advised as a first-line therapy for URTI in most guidelines, the results of the meta-analysis indicate that clarithromycin is nevertheless a valid, effective and largely well-tolerated treatment option for GABHS pharyngitis patients who cannot benefit from other agents.Keywords: clarithromycin, erythromycin, amoxicillin, Streptococcus, pharyngitis, metaanalysis